Breath odor-based individual authentication by an artificial olfactory sensor system and machine learning. Issue 44 (20th May 2022) - Jirayupat, Chaiyanut; Nagashima, Kazuki; Hosomi, Takuro; Takahashi, Tsunaki; Samransuksamer, Benjarong; Hanai, Yosuke; Nakao, Atsuo; Nakatani, Masaya; Liu, Jiangyang; Zhang, Guozhu; Tanaka, Wataru; Kanai, Masaki; et al.
Abstract : The potential feasibility of breath odor sensing-based individual authentication was demonstrated by a 16-channel chemiresistive sensor array and machine learning. Abstract : Breath odor sensing-based individual authentication was conducted for the first time using an artificial olfactory sensor system. Using a 16-channel chemiresistive sensor array and machine learning, a mean accuracy of >97% was successfully achieved. The impact of the number of sensors on the accuracy and reproducibility was also demonstrated.